2003
DOI: 10.1111/1467-9450.00353
|View full text |Cite
|
Sign up to set email alerts
|

Memories of mother, complementarity and shame: Predicting response to subliminal stimulation with “Mommy and I are one”

Abstract: A poorly understood finding with potentially wide-ranging implications is that subliminal stimulation with "Mommy and I are one" affects behavior. In this study (n= 62), "Mommy and I are one" lowered implicit mood (p= 0.0015) in comparison with a neutral stimulus ("People are walking"). The effect was most pronounced in shame-prone participants with less positive memories of their mother, and low self-mother complementarity (interaction p= 0.0044). Effects of a potentially shame-inducing stimulus ("I am comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Henry et al, 1986;Sohlberg, Claesson, & Birgegard, 2003;Svartberg & Stiles, 1992). It is, however, not a concept with unitary meaning or measurement.…”
Section: Complementaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Henry et al, 1986;Sohlberg, Claesson, & Birgegard, 2003;Svartberg & Stiles, 1992). It is, however, not a concept with unitary meaning or measurement.…”
Section: Complementaritymentioning
confidence: 99%
“…Henry et al (1986) defines complementarity as affiliation correspondence and interdependence reciprocity. Complementarity has been operationalized as correlations between aggregated cluster frequencies in interactions (e.g., Sohlberg et al, 2003), but more often it has been measured in transition and sequence analyses. Several researchers use complementarity to mean the adjacent speeches of two speakers in a transition that are given the identical cluster code or nearly the same cluster code (i.e., identical codes on both or only one SASB dimensions).…”
Section: Complementaritymentioning
confidence: 99%
“…For example, the anal message ‘GO SHIT’ could have produced similar variations on the stuttering index in schizophrenics, but that was not measured (Malik, ). It should be noted that more recent follow‐up studies with the ‘MOMMY AND I ARE ONE’‐prime have confirmed that the stimulus was able to produce persisting reductions in depression as well as other effects among students over a 2‐week period (Sohlberg and Birgegard, ; Sohlberg et al ., ). The persistence of positive results over decades indicates that the effects of this priming are very probably real, even if control and interpretation issues, proper to the SPA research, may have limited a wider impact of these results on the scientific community at large.…”
Section: Subliminal Priming Researchmentioning
confidence: 97%
“…Although suggestive only, data in one of their experiments were even consistent with effects lasting several months. The selection of these particular stimuli MIO and MIDIS was based on the well‐established effects of MIO (for a meta‐analysis see Hardaway, 1990; for a review see Weinberger & Hardaway, 1990; also see Sohlberg, Billinghurst & Nylén 1998; Sohlberg, Claesson & Birgegard, 2003; Sohlberg & Jansson, 2002). Participants were first seen individually in the laboratory and exposed to the stimuli, and ten days later they returned for a questionnaire session.…”
Section: Introductionmentioning
confidence: 99%